Development and validation of a quality of life scale in Familial Mediterranean Fever (FMFQoL) - DURUÖZ, MEHMET TUNCAY (TAYLOR & FRANCIS LTD, 2021)
Objective:To develop a valid and reliable quality-of-life (QoL) scale in familial Mediterranean fever (FMF). Methods:After producing question pool by using psychometric methods, high-performance questions were obtained according to expert panel. The principal component analysis (PCA) was done with varimax rotation for factor analysis. The final version of the scale (FMF-QoL) was examined for reliability and validity. Internal consistency with Cronbach alpha was calculated. The face, content, convergent and discriminant validity were analyzed. PRAS score used to assess the disease activity. Spearman correlation coefficient (rho) was used to assess the convergent and discriminant validity. Results:In our study, 123 FMF patients were recruited. According to the factor analysis the FMF-QoL were represented by 4 factor groups (eigenvalues >1) which were physical impact, social and recreational impact, psychological impact, and impact of sleep. All questions' factor loadings after Varimax rotation were bigger than 0.5 and the cumulative variance of the scale was 68.11%. The strongest correlation of the FMF-QoL was found with other QoL scales like EUROHIS (rho: -0.64,p < .0005) and Short Form 36 physical functioning subscale (rho: -0.63,p < .0005). The correlations between the FMF-QoL and functional parameters were found to be moderate [Beck Depression Inventory-Primary Care (rho: 0.46,p < .0005), Jenkins Sleep Scale (rho: 0.44,p < .0005), Health Assessment Questionnaire (rho: 0.44,p < .0005)]. FMF-QoL was also correlated with the disease specific measures [PRAS (rho: 0.42,p < .0005), number of attacks in the previous year (rho: 0.44,p < .0005)]. Conclusion:A valid, reliable, practical, not time-consuming FMF-specific QoL scale that can be used in the clinical follow-up and treatment of these patients was developed and validated.
Keywords: FMFQoL; FMF; quality of life; FMF-specific measure; Familial Mediterranean Fever; outcome measure; disease-specific measure; TURKISH VERSION; L-QOL; VALIDITY; RELIABILITY; INDEX; FRAMEWORK